1394. Impact of 7-Valent and 13-Valent Pneumococcal Conjugate Vaccines in the United States: A Systematic Literature Review. (31st December 2020) - Kistler, Kristin; Gomez-Espinosa, Evelyn F; Sutton, Kelly; Chapman, Ruth; Dillon-Murphy, Desmond; Wasserman, Matthew
Abstract: Background: The availability of 7-valent (PCV7) and 13-valent (PCV13) pneumococcal conjugate vaccines (PCVs) in the United States (US) since 2000 and 2010, respectively, has substantially reduced the occurrence, morbidity and mortality of pneumococcal disease. This systematic literature review aimed to assess the impact of the PCVs in reducing the pneumococcal disease burden since their introduction. Methods: We searched Embase and Medline and disease-surveillance websites for observational studies of US participants < 19 years, published 1999–2019 and reporting incidence or prevalence of acute otitis media, invasive pneumococcal disease, meningitis, or pneumococcal disease-related morbidity, mortality, healthcare resource utilization (HCRU) or costs. Results: Of 499 citations identified from the databases and other sources, 125 met inclusion criteria (Figure), all indicating clear reductions in multiple manifestations of pneumococcal disease with PCV7 and PCV13 use. However, variations across studies in outcomes reported, study years, and age strata, confounded assessment of vaccine impact on specific pneumococcal disease outcomes and key burden indicators, such as tympanostomy tube placement and antibiotic prescriptions. Conclusion: PCVs have greatly decreased multiple manifestations of pneumococcal disease in the US. However, granular data on the frequency and morbidity associated with specific pneumococcal diseases and on associated HCRU are needed to quantify the public-health impact of these vaccines. Disclosures: Kristin Kistler, PhD, Evidera, Inc. (Employee, Evidera, Inc. received the funding to conduct this study.) Evelyn F. Gomez-Espinosa, BSc, PhD, Evidera Inc (Employee, Scientific Research Study Investigator)Pfizer Inc (Consultant, Scientific Research Study Investigator) Kelly Sutton, PhD, Evidera (Other Financial or Material Support, Evidera, Inc. received the funding to conduct this study.) Ruth Chapman, MSc, PhD, Evidera, Inc, (Evidera, Inc. received the funding to conduct this study. ) (Consultant) Desmond Dillon-Murphy, MSc, PhD, Evidera, Inc. (Evidera, Inc. received the funding to conduct this study. ) (Consultant) Matthew Wasserman, MSc., Pfizer Inc. (Employee)